Bodies, beings, and the multiple burial rite of the Western Viking world - Ratican, Claire F., author.
1 online resource (volumes cm.)
Keywords: "This book explores multiple burials, the presence of more than one individual within a grave, within the Viking Age mortuary landscape throughout Scandinavia and the lands of their westward diaspora. Even though a number of spectacular examples have captured the imagination of professionals and the public alike, multiple burials have not been the subject of dedicated and systematic archaeological investigation. By adopting a perspective grounded in relationality and an analysis that centres on three types of beings- humans, animals and things- this book explores the ways in which each being entered into entangled relationships with the other, thereby mutually constituting the nature of their existence in Viking Age minds. For the first time, the corpus of Viking Age multiple burials located across the lands of the western Scandinavian diaspora and their counterparts in the urban trading centres of Kaupang (Norway) and Hedeby (formerly Denmark) is synthesised into a single study, firmly situating the multiple burial rite within the wider suite of normative burial practices observed across the Viking World. The book meaningfully engages with a developing discourse in the Scandinavian tradition increasingly revealing the fluidity of being across human, animal, and thing bodies in Iron Age mentalities and material culture. Ultimately, it poses the question: are humans, animals and things similar forms of bodies and beings in the Viking world? This book will appeal to students and researchers of death and burial in the Viking world"--